Translation, adaptation, and validation of the Filipino version of the Caring Behaviors Inventory - Reiner Lorenzo Tamayo; Dan Louie Renz Tating; Ericka Louise Gilo; Hannah Kristine Mugol; Karen Grace Laureta (Belitung Raya Foundation, Indonesia, 2022)
Background: The way patients perceive nurses’ caring behaviors can potentially impact patient outcomes and satisfaction. Studies have revealed incongruence between nurses’ and patients’ perceptions with regard to which behaviors are considered caring. Objective: This study aimed to conduct a cross-cultural validation and evaluation of the psychometric properties of the Caring Behaviors Inventory (CBI-16), a self-report questionnaire, from English to Filipino. Methods: A descriptive cross-sectional design involving forward and back-translation with bilingual translators, expert validation, and a survey in a sample of patients and nurses was used. The psychometric evaluation used a sample of 142 staff nurses and 180 hospitalized patients. Exploratory factor analysis, internal consistency reliability, and inferential statistics were used for data analysis. Results: The Filipino version of the CBI-16 (CBI-16-FIL) had excellent internal consistency (Cronbach’s alpha of 0.95) and a unidimensional factor structure (accounted for 85% of total variance). The CBI-16-FIL was found to be a valid, reliable, and unidimensional tool to measure the perceptions of nurse caring behaviors in the Philippines. Conclusion: The CBI-16-FIL can be used to measure perceptions of nurse caring behaviors. There is a need for further studies involving other cultures, dyadic samples of nurses and patients, and larger sample sizes.